P-330 The immune cell population of the human fallopian tubes in health and benign pathology: a systematic review. (30th June 2022) - Aljassim, F; Rigby, C; Powell, S; Wyatt, J; Hill, C; Hapangama, D
Abstract: Study question: What is the immune cell profile of the human fallopian tube in health and in benign pathological conditions? Summary answer: The fallopian tubes have a distinct population of immune cells from the innate and adaptive subsystems. Variations have been observed in several tubal pathologies. What is known already: The fallopian tubes play a key role in fertility; up to 30% of infertility cases have been reported due to tubal pathologies, which have been neglected due to the success of in vitro fertilisation (IVF). The fallopian tubes have been shown to harbour immune cell populations with the involvement of both the innate and adaptive arms of the immune system that provide surveillance against several pathogens. Therefore, characterisation of this population is vital in promoting a better understanding of tubal pathogenesis, and its influence on infertility, leading to improvements in the sexual and reproductive health of women. Study design, size, duration: This systematic review was conducted on the 1 st November 2021 and reported in accordance to PRISMA statement, and preceded by a prospectively written protocol registered with PROSPERO (registration number: CRD42021288257). CINAHL, EMBASE and EMCARE, Scopus and PubMed databases were searched for relevant published material. All studies that concerning the immune cells of human fallopian tubes in health or benign pathology of pre-menopausal, pregnant and/or post-menopausal women that published in English language were included. Participants/materials, setting, methods: The predefined search strategy identified 3767 publications. Following screening, a total of 42 studies were included and data was extracted. The findings are thematically reported based on: (1) menopausal status and/or cycle phase; (2) pathophysiology; (3) immune cell types. A risk of bias assessment was performed using Newcastle-Ottawa scale (NOS) and a modified version for case studies. Main results and the role of chance: T lymphocytes, predominantly CD8 + cytotoxic T cells, represent the most abundant immune cell population within the healthy fallopian tube. B lymphocytes, macrophages, natural killer (NK) cells and dendritic cells have also been identified. The number of macrophages demonstrated a consistent and significant increase during the progesterone-dominant secretory phase compared to the proliferative phase. A similar distribution of lymphocytes was reported in tubal ectopic pregnancies to that in healthy tubes. Macrophages, dendritic cells, and natural killer (NK) cells were observed in tubal pregnancies with a significant increase in the number of CD56 + and CD3 + cells in cases of tubal rupture. Salpingitis, hydrosalpinx and endometriosis are all characterised by an increased population of macrophages in comparison to healthy fallopian tubes. Limitations, reasons for caution: Some studies scored poorly on the NOS, suggesting their findings to be treated with caution. The deficiency in published research into common tubal pathologies and inconsistent findings presented between studies only allowed limited conclusions to be formulated regarding these immune cell populations. Wider implications of the findings: Comprehensive knowledge of the immune cell profile of the human fallopian tubes will provide greater understanding into the pathophysiology of common tubal disorders, potentially leading to innovative treatments in the future. Trial registration number: not applicable